Visfatin Promotes Renal Cell Carcinoma Progression: Evidence from Clinical Samples and Cell Line Models (Journal of Kidney Cancer, 2025)
The kidney is enveloped by perirenal fat, which secretes various hormones and cytokines, known as adipokines. Adipokines have been demonstrated to influence the development and progression of tumors, including renal cell carcinoma (RCC). Visfatin, an adipokine secreted by the adipose tissue, has been implicated in RCC, but its precise role remains unclear. In this study, we investigated the expression of visfatin in perire-nal fat from patients with RCC and its correlation with the RCC malignant phenotype, and we examined the role of visfatin in RCC cell lines in vitro. This study included adipose tissue samples from 57 Japanese patients with clear cell RCC who underwent partial or radical nephrectomy. We examined the mRNA expression level of visfatin using real-time PCR. In vitro MTT assay and western blot were performed using human RCC cell lines. The mRNA expression of visfatin in peri-tumor versus peri-normal fat was higher in Fuhrman grade ≥2 cases compared with Fuhrman grade 1 cases. Furthermore, the addition of visfatin to RCC cell lines promoted cell proliferation, which was accompanied by increased protein expression of HIF1α, p-Akt, and p-ERK. Conversely, the addition of FK866, a visfatin inhibitor, suppressed cell proliferation and reduced these proteins. Our findings suggest that visfatin from peri-tumor adipose tissue influences the malignancy of RCC and plays a role in promoting the growth of RCC. This indicates a potential mechanism by which adipose tissue contributes to the progression of RCC, providing a possible target for therapeutic intervention.